Novel zero-current-switching PWM step down Sepic converter - Sobrinho, L. T.S. [UNESP]; Kitamura, R. A. [UNESP]; Canesin, C. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1998)
This paper presents a new step down PWM (pulse width modulation) Sepic (single ended primary inductance converter) converter, featuring soft commutation at zero-current (ZCS), using IGBTs (insulated gate bipolar transistors) as the power switches. This new ZCS-PWM cell provides conditions to obtain a new family of isolated converters. The new ZCS-PWM Sepic converter is used to provide output voltage lower than input voltage, and high efficiency for a wide load range. Thus, providing a great reduction in the heat sinks size used. This new PWM converter provides zero-current (ZC) turn-on and zero-voltage-zero-current (ZVZC) turn-off of the active switches, and it is suitable for IGBTs applications. It should be noticed that the diodes D1 and D2 are also softly commutated under zero-voltage switching (ZVS). The principle of operation, the theoretical analysis, a design example, and experimental results from a laboratory prototype rated at 300 W with 220 Vdc nominal input voltage, 51 Vdc output voltage, and 20 kHz switching frequency are reported to validate the theoretical analysis.